2016
DOI: 10.1021/acs.energyfuels.5b02562
|View full text |Cite
|
Sign up to set email alerts
|

Low Salinity Effect at Pore Scale: Probing Wettability Changes in Middle East Limestone

Abstract: The effectiveness of low salinity flooding for enhanced oil recovery (EOR) in sandstone reservoirs has been demonstrated in core plug and field tests as well as at molecular scale, but in carbonate reservoirs the results are mixed. With atomic force microscopy (AFM) chemical force mapping (CFM), using a methyl (CH3) functionalized tip, we tracked the wettability of limestone pore surfaces (before and after solvent treatment) during exposure to high and low salinity solutions at a submicrometer scale. The corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…In the biological community and in recent literature related to reservoir fluids, researchers have studied adhesion at the nanoscale to understand the effects of overall salinity on nanomaterial adhesions, mineral dissolution, molecular adhesion related to protein-protein interactions, and even wettability of reservoir surfaces 35 , 51 , 56 , 59 , 64 89 . In such studies, increasing overall salinity increases adhesion, which then plateaus 36 , 38 , 73 , 74 , 77 , 79 81 . In addition, changes in the interaction forces can be used to link more adhesive areas to mineralogical composition and with changes in wettability 76 , 81 , 84 , 85 .…”
Section: Introductionmentioning
confidence: 99%
“…In the biological community and in recent literature related to reservoir fluids, researchers have studied adhesion at the nanoscale to understand the effects of overall salinity on nanomaterial adhesions, mineral dissolution, molecular adhesion related to protein-protein interactions, and even wettability of reservoir surfaces 35 , 51 , 56 , 59 , 64 89 . In such studies, increasing overall salinity increases adhesion, which then plateaus 36 , 38 , 73 , 74 , 77 , 79 81 . In addition, changes in the interaction forces can be used to link more adhesive areas to mineralogical composition and with changes in wettability 76 , 81 , 84 , 85 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work, for example, has demonstrated that adsorbed organic compounds, which are associated with all natural surfaces, change wetting properties 13,14 . Although crude oil is a complex mixture of many organic compounds, it is primarily the functional groups that deter- mine which adhere on the pore surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Precisely controlling the effective wetting properties of droplets in immiscible two-phase flows is desirable in many applications, from fabricating microfluidic devices [1][2][3] and electronic displays [4][5][6][7] to understanding the microscopic dynamics of enhanced oil recovery, which has field-scale consequences [8][9][10][11][12]. Lippmann already in the 19th century [13,14] laid the groundwork for the field of electrowetting, by making the observation that applying an electric field indeed can change the wetting behaviour of conductive liquid-liquid systems.…”
Section: Introductionmentioning
confidence: 99%